Misconceptions of Religious Freedom: Toward an Empirical Study of Religious Freedom Awareness - Blasi, Anthony J. (Religions, 2023)
This article offers an overview of the most common misconceptions about religious freedom, with reference to the 2017 UN Report by Mr. Shaheed and the perspectives of other human rights scholars and experts. It proceeds with the operationalization of a selected list of misconceptions about this subject for empirical research of religious freedom awareness. We discuss the primary results from a survey on social perceptions of religious freedom collected from a convenience sample of university students in Northern Italy (N = 1035), offering, first, a new scale of religious freedom awareness (RFA), and second, a consideration of its association with various dimensions of religious freedom and other human rights. The findings show that awareness of religious freedom serves as a robust predictor of endorsement of a broader set of human rights by participants, including those potentially antithetical to religious freedom claims, such as gay and women’s rights. We discuss these findings against a holistic approach to human rights and empirical evidence that other variables (political engagement, passive secularism views, and spiritual identity) contribute to the endorsement of rights culture in Italian society.